Tracing the Anharmonicity and Superionic Phase Transition of Hydrous FeO2H - Hu, Qingyang; Tang, Mingxue (Frontiers in Earth Science, 2022)
The weak x-ray scattering of hydrogen (H) has brought major challenges for the characterization of superionic transitions in high-pressure ice, hydrides and hydroxides. Combining first-principles molecular dynamics and simulated nuclear magnetic resonance (NMR) spectroscopy, we investigate the behavior of the hydroxyl bonding and structural transitions in the hydrous FeO2H between 300 and 2750 K and up to 130 GPa. Evidences show an intermediate plastic state with regional H diffusion and anharmonic O-H vibration exists in between the ordinary solid and the superionic phase. The intermediate state features asymmetric hydrogen bonds and anharmonic vibrations, which is readily being distinguished from the high-temperature superionic phase. Our work shows NMR is a more sensitive probe to detect H diffusion in superionic solids even at the extreme conditions of Earth’s deep interiors.